Concurrent cisplatin and dose escalation with intensity-modulated radiotherapy (IMRT) versus conventional radiotherapy for locally advanced head and neck squamous cell carcinomas (HNSCC): GORTEC 2004-01 randomized phase III trial. (September 2020) - Tao, Yungan; Auperin, Anne; Blanchard, Pierre; Alfonsi, Marc; Sun, Xu-Shan; Rives, Michel; Pointreau, Yoann; Castelli, Joël; Graff, Pierre; Wong Hee Kam, Stéphanie; Thariat, Juliette; Veresezan, Ovidiu; et al.
Highlights: Xerostomia was markedly decreased with IMRT vs 3D in LA-HNSCC in a phase 3 trial. This dose-escalation with IMRT (75 Gy) was well tolerated with high dose cisplatin. Dose-escalated IMRT did not improve tumor control over standard 3D-RT in HNSCC. Abstract: Background: Concurrent chemoradiotherapy (CRT) is the standard of care (SoC) in locally advanced (LA) head and neck squamous cell carcinomas (HNSCC). This trial was designed to test whether dose-escalated IMRT and cisplatin could improve locoregional control without increasing complications over 3D-radiotherapy. Methods: Patients were randomized between 70 Gy/35F in 7 weeks with 3D-RT (Arm A) versus 75 Gy/35F with IMRT (Arm B). Both arms received 50 Gy in 25 fractions followed by a sequential boost of 20 Gy/10F in Arm A and 25 Gy/10F to gross tumor volume in Arm B, as well as 3 cycles of cisplatin at 100 mg/m2 during RT. The primary endpoint was locoregional progression (LRP). Results: 188 patients were randomized: 85% oropharynx and 73% stage IVa. P16 status was documented for 137 oropharyngeal tumors with P16+ in 53 (39%) patients; and 90% were smokers. Median follow-up was 60.5 months. Xerostomia was markedly decreased in arm B ( p  < 0.0001). The 1-year grade ≥2 xerostomia (RTOG criteria) was 63% vs 23% and 3-year 45% vs 11% in arms A and B, respectively. Xerostomia LENT-SOMA scale was also reduced in arm B. Dose-escalated IMRT did not reduce LRP with an adjusted HR of 1.13 [95%CI = 0.64–1.98] ( p  = 0.68). Survival was not different (adjusted HR: 1.19 [95%CI = 0.78–1.81], p  = 0.42). No interaction between p16 and treatment effect was found. Conclusion: Dose-escalated IMRT did not improve LRC in LA-HNSCC patients treated with concomitant CRT over standard 3D-RT. This trial reinforces the evidence showing IMRT reduces xerostomia in LA-HNSCC treated with radiotherapy. Clinicaltrial.gov: NCT00158678.